Enhancing wound healing with synthetic hyaluronic acid injection in sutured incisions on BALB/c mice - Elham Aryanfar; Mahdi Ghoncheh; Mohammad Afshar; Mahboobe Chahkandi; Elahe Allahyari; Mehri Shadi (Folia Medica)
Introduction: Hyaluronic acid has been shown to possess notable properties in wound healing, skin regeneration, and anti-inflammatory effects. The formation of scar tissue is a common and unintended phenomenon during the wound-healing process, potentially leading to diverse consequences for individuals. Aim: The objective of this study was to investigate the effect of injecting synthetic hyaluronic acid on the wound healing process in BALB/c mice subjected to suture wounding. Materials and methods: In this experimental study, 18 adult male BALB/c mice were utilized and distributed into two groups (9 mice each): an experimental group and a control group. A full-thickness incision wound, one centimeter in length, was created in the skin of the back neck area for both groups. After being wounded, all wounds were sutured. However, only mice in the experimental group had 0.05 mL of hyaluronic acid on both sides of the wound. On days 7, 14, and 21 following the injection of hyaluronic acid, three mice from each group were anesthetized, and skin samples were collected for histological evaluation. After staining the tissue slides with hematoxylin-eosin and Masson’s trichrome, a comprehensive analysis was conducted by a pathologist to quantify key histological parameters, including the number of fibroblasts, collagen fiber density, granulation area, and epithelium thickness. Results: The experimental group demonstrated an increased number of fibroblasts, higher collagen density, and a more organized arrangement of collagen fibers when compared to the control group. On day 21, the experimental group exhibited a significantly higher average thickness of the epithelium and greater hair growth when compared to the control group. Conclusion: Our findings suggest that hyaluronic acid exerts a positive influence on the healing process of sutured incisions, positioning it as a promising candidate for preventing the formation of abnormal scars at the site.